HUBUNGAN KEDISIPLINAN TERHADAP PRESTASI KERJA PEGAWAI PADA SEKRETARIAT DAERAH KABUPATEN KUBU RAYA - Simon Ahie (STIE 'INDONESIA' Pontianak, 2013)
The research was conducted on government institution in West Kalimantan with the purpose to identifying relation between disciplines as independent variable to the performance. This study use chi square analysis to provide result about the set of problem. This study also uses 30 respondents as an object. Based on study analysis, that disciplines didn’t have relation to the performance. From chi square analysis find X2 statistic (7.67) ≤ X2 table, that mean no relation between disciplines and performance.